Multi‐objective optimization for facilities management - Brauers, Willem K. (Journal of Business Economics and Management, 2004)
The main point of this article is to present in a short text all aspects of Multi ‐ Objective Optimization for Facilities Management, so to say from the cradle until the grave. Additionally, the combination of Multi ‐ Objective Optimization with Nominal Methods and Scenario Writing represents an innovation. It is also stated that all stakeholders interested in the issue, instead of one decision maker, have to be involved. First, desk research will discover all the surrounding conditions of the issue under consideration. Therefore, during a period of creative thinking in a nominal exercise all the main influencing events are recorded and finally ranked. From this information, scenarios for the future of the facilities sector are deduced. On basis of all these data, objectives and alternatives are simulated. A Multi ‐ Objective Optimization for the facilities sector is made possible by two methods: an additive method with ratios and the application of Reference Point Theory. Automatically, using these methods, all objectives are normalized to dimensionless numbers between zero and one. Nevertheless, a problem of importance for each objective may remain. Therefore, two methods are proposed. First, weights are granted in a nonlinear way. Secondly, an objective becomes more important by introducing different attributes for the same objective. The latter method seems to be more refined. In this way, a final ranking of the alternatives for the fulfillment of the objectives is obtained.First Published Online: 14 Oct 2010